232k views
2 votes
What is the solution to this equation?


2x + 3 = x − 4

User Elyas
by
5.8k points

2 Answers

5 votes

Answer:

X=7

Explanation:

Step 1

Having all the

x

terms on one side of =

Subtract

2 x

from both sides

2 x − 2 x + 3 = 3 x − 2 x − 4

0 + 3 = x − 4

Swap round

x − 4 = 3

Step 2

Have just

x

on the left of =

Add

4

to both sides

x − 4 + 4 = 3 + 4

x = 7

User BontoJR
by
5.8k points
1 vote

Answer:

x = −7

Explanation:

2x + 3 = x − 4

Subtract 3 from both sides of the equation

2x = x −7

Subtract x from both sides of the equation

x = −7

User Pshemo
by
6.2k points